Qanā‘ah dan Pengaruhnya Terhadap Kesehatan Jiwa Menurut Buya Hamka dalam Tafsir Al-Azhar - Sri Melati; Ahmad Zuhri; Jufri Naldo (Jurnal test, 2025)
This research focuses on the study of the concept of qanā’ah and its influence on mental health according to Buya Hamka in Tafsir al-Azhar. The purpose of this research is to explain how Buya Hamka interprets verses related to qanā’ah and its relevance to mental health. The research method used is a qualitative method with a library research approach. The primary source of this research is Tafsir al-Azhar by Buya Hamka, while secondary sources consist of classical and contemporary tafsir books, Sufism books, and Islamic psychology literature. Data analysis was carried out using the thematic method (maudhu’i). The results of the study indicate that qanā’ah according to Buya Hamka includes five dimensions: accepting willingly for what is there, asking for additional sustenance with appropriate efforts, being patient with Allah’s provisions, putting one’s trust in Allah, and not being attracted to the deceit of the world. This concept, when applied, functions as a self-control mechanism that can prevent the emergence of heart diseases such as envy, jealousy, greed, and complaints. From an Islamic psychological perspective, contentment can foster inner peace, gratitude, optimism, and resilience in the face of life’s difficulties. Thus, contentment is not merely a spiritual value but also significantly contributes to achieving individual mental health and social harmony.